Handbook of food process modeling and statistical quality control : with extensive MATLAB applications - Ozilgen, Mustafa; t (Boca Raton, FL : CRC Press, 2011)
'Presenting mathematical prerequisites in summary tables, this book explains fundamental techniques of mathematical modeling processes essential to the food industry. The author focuses on providing an in-depth understanding of modeling techniques, rather than the finer mathematical points. Topics covered include modeling of transport phenomena, kinetic processes, and food engineering operations. The book also discusses statistical process analysis and quality control. It includes examples from almost every conceivable food process, most of which are based on real data given in the many references. Each example is followed by a clear, step- by-step worked solution'--Provided by publisher.
'The second edition of the book is substantially different from the first edition in the sense that i. The title of the book is modified following the recommendations of experts from academia and the industry. It is intended to present the book as a compendium of applications within its scope. ii. The new edition covers extensive MATLAB applications. The model equations are solved with MATLAB and the resulting figures are generated by the code. The models are compared mostly with real data from the literature. Some errors occurred while reading the data; therefore, the model parameters sometimes had different values than those of the references. iii. Tabular values and plots of mathematical functions are produced through MATLAB codes. iv. All of the MATLAB codes are given on the CD accompanying the book. A summary of the important features and functions of the MATLAB codes used in the book are given in Table 1.1. The readers may refer to this table to locate the functions or syntax they need. They may copy lines from the examples and write their own code with them. I wrote my own codes by following this procedure. I would recommend achieving each task in the code in a stepwise manner and then going on to the next task. Each task is usually defined in the examples with phrases such as x Preface % enter the data, % plot the data, % modeling, % plot the model, etc. I tried to maintain this order in the codes when possible. v. A few food processing methods (i.e., pulsed electric field and high pressure processing) gained importance after the first edition. Some examples are included to cover the development'--Provided by publisher.
Machine generated contents note: 1. Introduction to Process Modeling -- 1.1. The Property Balance -- 1.2. What Is Process Modeling? -- 1.3. Empirical Models and Linear Regression -- References -- 2. Transport Phenomena Models -- 2.1. The Differential General Property Balance Equation -- 2.2. Equation of Continuity -- 2.3. Equation of Energy -- 2.4. Equation of Motion -- 2.5. Theories for Liquid Transport Coefficients -- 2.5.1. Eyring's Theory of Liquid Viscosity -- 2.5.2. Thermal Conductivity of Liquids -- 2.5.3. Hydrodynamic Theory of Diffusion in Liquids -- 2.5.4. Eyring's Theory of Liquid Diffusion -- 2.6. Analytical Solutions to Ordinary Differential Equations -- 2.7. Transport Phenomena Models Involving Partial Differential Equations -- 2.8. Chart Solutions to Unsteady State Conduction Problems -- 2.9. Interfacial Mass Transfer -- 2.10. Correlations for Parameters of the Transport Equations -- 2.10.1. Density of Dried Vegetables -- 2.10.2. Specific Heat -- 2.10.3. Thermal Conductivity of Meat -- 2.10.4. Viscosity of Microbial Suspensions -- 2.10.5. Moisture Diffusivity in Granular Starch -- 2.10.6. Convective Heat Transfer Coefficients during Heat Transfer to Canned Foods in Steritort -- 2.10.7. Mass Transfer Coefficient k for Oxygen Transfer in Fermenters -- 2.11. Rheological Modeling -- 2.12. Engineering Bernoulli Equation -- 2.13. Laplace Transformations in Mathematical Modeling -- 2.14. Numerical Methods in Mathematical Modeling -- References -- 3. Kinetic Modeling -- 3.1. Kinetics and Food Processing -- 3.2. Rate Expression -- 3.3. Why Do Chemicals React? -- 3.4. Temperature Effects on Reaction Rates -- 3.5. Precision of Reaction Rate Constant and Activation Energy Determinations -- 3.6. Enzyme-Catalyzed Reaction Kinetics -- 3.7. Analogy Kinetic Models -- 3.8. Metabolic Process Engineering -- 3.9. Microbial Kinetics -- 3.10. Kinetics of Microbial Death -- 3.11. Ideal Reactor Design -- References -- 4. Mathematical Modeling in Food Engineering Operations -- 4.1. Thermal Process Modeling -- 4.2. Moving Boundary and Other Transport Phenomena Models for Processes Involving Phase Change -- 4.3. Kinetic Modeling of Crystallization Processes -- 4.4. Unit Operation Models -- 4.4.1. Basic Computations for Evaporator Operations -- 4.4.2. Basic Computations for Filtration and Membrane Separation Processes -- 4.4.3. Basic Computations for Extraction Processes -- 4.4.4. Mathematical Analysis of Distilled Beverage Production Processes -- References -- 5. Statistical Process Analysis and Quality Control -- 5.1. Statistical Quality Control -- 5.2. Statistical Process Analysis -- 5.3. Quality Control Charts for Measurements -- 5.4. Quality Control Charts for Attributes -- 5.5. Acceptance Sampling by Attributes -- 5.6. Standard Sampling Plans for Attributes -- 5.7. HACCP and FMEA Principles -- 5.8. Quality Assurance and Improvement through Mathematical Modeling -- References.
Rev. ed. of: Food process modeling and statistical quality control. 1998.
Book is accompanied by one CD entittled' Handbook of food process modeling and statistical quality control
Includes bibliographical references and index.
Keywords: Food industry and trade -- Production control -- Mathematical models; Food industry and trade -- Quality control -- Statistical methods; CD-ROMs.